2018
DOI: 10.1364/ao.57.004409
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the optical center position of an optical system of a camera lens

Abstract: A theory of an optical center of a camera lens is described. The concept of an optical center (a camera center) is used widely in various methods dedicated to the calibration of optical imaging and measuring systems in photogrammetry, computer vision, triangulation sensors, fringe projection techniques, surveying, and machine vision, where the so-called pinhole camera model is used as the camera's basic model. It is shown that the optical center of the optical system with a fixed position does not exist genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As a simplified approximate model, pinhole camera model simply and effectively provides the projection between object and image. However, some studies [3] indicated the error of this approximation in defocused image. Modeling according to the ideal optical system is a more accurate approximation of the camera imaging process.…”
Section: Principle 21 Optical System Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…As a simplified approximate model, pinhole camera model simply and effectively provides the projection between object and image. However, some studies [3] indicated the error of this approximation in defocused image. Modeling according to the ideal optical system is a more accurate approximation of the camera imaging process.…”
Section: Principle 21 Optical System Modelingmentioning
confidence: 99%
“…Mikš and Novák [3] analyzed the ideal optical system of the camera and calculated the difference between the optical center coordinates of the central projection system and the ideal optical system. Bothe et al [4] built the vision ray calibration (VRC), which directly modeled the optical system as a black box, tracing each pixel individually, providing a more accurate calibration method in the optical caustic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Many projectors are designed to project off-axis and their principal points are often outside imaging planes. As a result, residual distortion is usually observed [20,21], despite the use of depth-dependent pinhole models [22]. For example, Yang et al [9] compensates residual distortion using a calibrated lookup table.…”
Section: Projector Distortion Modelmentioning
confidence: 99%